Peculiarities of grounds of civil liability for environmental damage - N V Ivanovskaya (RUDN Journal of Law, 2008)
The article deals with lively debated questions relating to the independence of liability for environmental damage. The author also pays attention to the peculiarities of grounds of such a liability, analyses both russian and foreign laws establishing liability for environmental damage resulting from activities of sources of heightened danger.